Late Quaternary megafaunal extinctions in India: How much do we know?. (15th January 2021) - Turvey, Samuel T.; Sathe, Vijay; Crees, Jennifer J.; Jukar, Advait M.; Chakraborty, Prateek; Lister, Adrian M.
Abstract: Understanding global patterns of late Quaternary megafaunal extinction is impeded by geographic variation in data quality and quantity. The magnitude, timing and drivers of megafaunal extinctions remain poorly understood for India, a region with a strong history of palaeontological research. We review available data for all putative extinct Indian megafaunal taxa with direct or indirect reported evidence of potential survival into the global "megafaunal extinction window" (from ∼50, 000 years onwards). Assessment of late Quaternary megafaunal species richness is confused by multiple levels of taxonomic uncertainty, including the relationship of named Late Pleistocene taxa to extant taxa, and nomenclatural confusion over correct species names. There is sufficient evidence to recognise up to four genuine global megafaunal species-level extinctions in India during the Late Pleistocene: two proboscideans ( Palaeoloxodon namadicus, Stegodon sp.), a hippopotamus ( Hexaprotodon sp.), and possibly a horse ( Equus namadicus ). A fifth extinct megafaunal species, the Indian aurochs Bos [ primigenius ] namadicus, definitely persisted into the Holocene. Other Indian late Quaternary megafaunal species ( Rhinoceros spp., Bubalus palaeindicus, Sus " palaeindicus ", Crocodylus palaeindicus ) are likely to be synonyms of extant species. Reconstructing regional extinction dynamics is further impeded by chronological uncertainty; however, attempts to obtain new dates for vertebrate samples from six late Quaternary sites in five regions were unsuccessful. Accurate understanding of the dynamics of megafaunal extinctions in India will require robust taxonomic, chronological and palaeoecological data, and we encourage further investigation of the region's rich late Quaternary record. Highlights: The magnitude and timing of megafaunal extinctions are poorly understood for India. We review all extinct Indian megafauna that possibly survived beyond c.50, 000 ka. Indian megafaunal extinctions are confused by taxonomic and dating uncertainty. We recognise up to four Late Pleistocene megafaunal species extinctions in India.